Digital inclusive finance, consumption structure upgrading and carbon emissions - Ye, Jian; Xu, Wenhua; Hu, Lujing (Frontiers in Environmental Science, 2023)
The "14th Five-Year Plan" represents a crucial phase in enhancing financial inclusivity in China and addressing the challenge of "peak carbon emissions." Given the digital economy's rapid growth, China must urgently devise a model for high-quality development that combines digital finance with eco-friendly and low-carbon strategies. Uniquely focusing on the intersection of digital finance and sustainable growth, this paper fills a critical gap in the existing literature. To examine the impact of digital inclusive financing on carbon emissions from the vantage point of enhancing consumption structures, this study uses panel data covering the years 2014 to 2020 from 30 Chinese provinces. This research underscores the novel finding that digital inclusive finance can play a significant role in lowering carbon emissions by encouraging individuals to alter their consumption patterns. Variations across regions are evident in the impact, with the central and western areas experiencing a more pronounced decline in carbon emissions in comparison to the eastern region. Moreover, the influence of consumption structure upgrading varies across regions. Additionally, the study identifies a positive spatial spillover relationship between digital inclusive finance and carbon emissions. Through its pioneering exploration, this study offers fresh insights for boosting digital finance's carbon-reduction impacts through consumption structure upgrades, strengthening the spatial interconnectedness of digital finance and consumption trends, and eventually supporting a path toward low-carbon, high-quality development.